IL-36γ is secreted through an unconventional pathway using the Gasdermin D and P2X7R membrane pores - Manzanares-Meza, Laura D.; Gutiérrez-Román, Claudia I.; Jiménez-Pineda, Albertana; Castro-Martínez, Felipe; Patiño-López, Genaro; Rodríguez-Arellano, Eunice; Valle-Rios, Ricardo; Ortíz-Navarrete, Vianney F.; Medina-Contreras, Oscar (Frontiers in Immunology, 2022)
Mucosal innate immunity functions as the first line of defense against invading pathogens. Members of the IL-1 family are key cytokines upregulated in the inflamed mucosa. Inflammatory cytokines are regulated by limiting their function and availability through their activation and secretion mechanisms. IL-1 cytokines secretion is affected by the lack of a signal peptide on their sequence, which prevents them from accessing the conventional protein secretion pathway; thus, they use unconventional protein secretion pathways. Here we show in mouse macrophages that LPS/ATP stimulation induces cytokine relocalization to the plasma membrane, and conventional secretion blockade using monensin or Brefeldin A triggers no IL-36γ accumulation within the cell. In silico modeling indicates IL-36γ can pass through both the P2X7R and Gasdermin D pores, and both IL-36γ, P2X7R and Gasdermin D mRNA are upregulated in inflammation; further, experimental blockade of these receptors’ limits IL-36γ release. Our results demonstrate that IL-36γ is secreted mainly by an unconventional pathway through membrane pores formed by P2X7R and Gasdermin D.